Gambaran Pola Peresepan Dan Rasionalitas Terapi Pada Pasien Hipertensi Di Puskesmas Banjarbaru Selatan Periode Januari-Juni 2023 - Indrawan, Dede; Yulistia Budianti; Aris Fadillah (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background:  Rational drug prescribing must follow a logical decision-making process starting from the collection of patient data through anamnesis, physical examination, laboratory tests, or other supporting examinations. The rational use of drugs in hypertension patients is very important to ensure cost-effectiveness, prescription accuracy, and drug use, as well as to improve the quality of healthcare services by evaluating indications, patients, drugs, and appropriate dosages. Objective: This study aims to understand the pattern of prescription and the rationality of therapy in hypertension patients at the Banjarbaru Selatan Health Center during the period of January - June 2023. Methods: This descriptive study uses a retrospective approach with the collection of secondary data from medical records, including age, gender, diagnosis, type of medication, medication class, medication category, indication, usage instructions, and dosage for hypertension patients over a period of 10 days. Results: The prescription pattern for patients based on drug class and type is the Calcium Channel Blockers (CCB) class and the amlodipine type at 95.7%. All hypertension patients received single antihypertensive drug therapy at 100%. Based on the usage rules and drug dosage, the type of drug amlodipine 1x1 was 51.60%. The rationality of antihypertensive therapy in the rational category was 98.39%, including 100% correct patients, 100% correct indication, 100% correct drug, 98.39% correct dosage, and 98.39% correct administration interval. Conclusion: The pattern of prescriptions based on drug class and type of drug used is the Calcium Channel Blockers (CCB) class and the type of drug amlodipine at 95.7%, and the depiction of the rationality of hypertension treatment therapy with a rationality of 98.39% at the Banjarbaru Selatan Health Center for the period January-June 2023.